2005
DOI: 10.2320/jinstmet.69.997
|View full text |Cite
|
Sign up to set email alerts
|

Internal Friction of Ultrafine-Grained Nickel Produced by Accumulative Roll-Bonding(ARB)

Abstract: Internal friction (Q -1 ) of nickel sheets highly deformed up to an equivalent strain (e) of 4.8 by the Accumulative Roll Bonding (ARB) process was investigated in order to clarify the damping mechanism of the ultrafine grained materials produced by severe plastic deformation. Although the strength increased with increasing number of the ARB cycle (N ), the maximum value of Q -1 was obtained at N=4 (e=3.2). At relatively small e about 1, where dislocation cell structure was formed, relatively small Q -1 belo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 16 publications
(4 reference statements)
0
3
0
Order By: Relevance
“…6,7) R. R. Mulyukov et al 8) and Y. Koizumi et al 9,10) reported that ultra-fine grained metals have large internal friction together with high strength, although highstrength materials generally have low damping capacity (internal friction). 11,12) Interesting properties of nano-structured materials are related to the largely increased density of lattice defects such as large angle grain boundaries and dislocations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…6,7) R. R. Mulyukov et al 8) and Y. Koizumi et al 9,10) reported that ultra-fine grained metals have large internal friction together with high strength, although highstrength materials generally have low damping capacity (internal friction). 11,12) Interesting properties of nano-structured materials are related to the largely increased density of lattice defects such as large angle grain boundaries and dislocations.…”
Section: Introductionmentioning
confidence: 99%
“…11,12) Interesting properties of nano-structured materials are related to the largely increased density of lattice defects such as large angle grain boundaries and dislocations. 6,[8][9][10][13][14][15] However, application of these techniques is limited to relatively low-strength materials. T. L. Brown et al 16) and S. Swaminathan et al 17) proposed a lowcost cutting process for production of nano-structured metals and alloys with very high hardness.…”
Section: Introductionmentioning
confidence: 99%
“…3,4) Interesting properties of these materials are related to the largely increased density of lattice defects such as large angle grain boundaries and dislocations. 1,[3][4][5][6][7][8] Severe plastic deformation techniques such as equal channel angular pressing (ECAP), [9][10][11] high pressure torsion (HPT) 12) and accumulative roll-bonding (ARB) 13) have been developed for production of nano-structured materials. However, application of these techniques is limited to relatively low-strength materials.…”
Section: Introductionmentioning
confidence: 99%